Fire and functional traits: Using functional groups of birds and plants to guide management in a fire‐prone, heathy woodland ecosystem. (7th April 2021) - Rainsford, Frederick W.; Kelly, Luke T.; Leonard, Steve W. J.; Bennett, Andrew F.
Abstract: Aim: Many dry forests and woodlands worldwide are fire‐prone and support bird and plant communities shaped by fire. Changes in fire regimes, including the time between fires, have important implications for population trajectories. We studied the responses of bird and plant communities of heathy woodlands to time since the last fire, a key measure underpinning fire management, to evaluate whether current management strategies will enhance conservation of multiple taxa. Location: Otway Ranges, south‐eastern Australia. Methods: We surveyed birds and plants at 38 sites, stratified by an 80‐year post‐fire chronosequence, and modelled the responses of individual species, functional groups and community composition to fire history. Model outputs were used to evaluate the impacts of fire management as guided by (a) domains of tolerable fire intervals, a concept based on plant life history traits, and (b) the spatial arrangement of post‐fire age classes, a surrogate for animal habitats. Results: Bird and plant communities both responded to time since fire. Notable relationships included the following: a high reporting rate of ground‐foraging birds and high cover and species richness of shrubs immediately after fire; and a gradual increase up to 50 years and 20 years post‐fire of birds that forage in the mid‐storey and facultative‐resprouting plants, respectively. Post‐fire age classes had distinct bird and plant assemblages. Tolerable fire intervals currently used by land managers (min 12–max 45 years between fires) encompassed the peak in richness of most plant functional groups but not the preferred habitat of lower‐mid‐storey foraging birds. Main conclusions: Fire management based solely on birds or plants risks population declines in other biota. Use of functional groups can help guide strategic planning, such as spatial representation of post‐fire age classes across the landscape. Maintaining late‐successional vegetation will provide habitat for several groups of birds, while fire is needed at sufficient frequency to prevent loss of plants and ground‐foraging birds.